Gamma Oryzanol Treats Obesity-Induced Kidney Injuries by Modulating the Adiponectin Receptor 2/PPAR-alpha Axis - Francisqueti, Fabiane Valentini [UNESP]; Togneri Ferron, Artur Junio [UNESP]; Hasimoto, Fabiana Kurokawa [UNESP]; Rizzi Alves, Pedro Henrique [UNESP]; Garcia, Jessica Leite [UNESP]; Santos, Klinsmann Carolo dos [UNESP]; Moreto, Fernando [UNESP]; Silva, Vanessa dos Santos [UNESP]; Ferreira, Ana Lucia A. [UNESP]; Minatel, Igor Otavio [UNESP]; Corrêa, Camila Renata [UNESP] (Hindawi Ltd, 2018)
The kidney is an important organ in the maintenance of body homeostasis. Dietary compounds, reactive metabolites, obesity, and metabolic syndrome (MetS) can affect renal filtration and whole body homeostasis, increasing the risk of chronic kidney disease (CKD) development. Gamma oryzanol (gamma Oz) is a compound with antioxidant and anti-inflammatory activity that has shown a positive action in the treatment of obesity and metabolic diseases. Aim. To evaluate the effect of gamma Oz to recover renal function in obese animals by high sugar-fat diet by modulation of adiponectin receptor 2/PPAR-alpha axis Methods. Male Wistar rats were initially randomly divided into 2 experimental groups: control and high sugar-fat diet (HSF) for 20 weeks. When proteinuria was detected, HSF animals were allocated to receive gamma Oz or maintain HSF for more than 10 weeks. The following were analyzed: nutritional and biochemical parameters, systolic blood pressure, and renal function. In the kidney, the following were evaluated: inflammation, oxidative stress, and protein expression by Western blot. Results. After 10 weeks of gamma Oz treatment, gamma Oz was effective to improve inflammation, increase antioxidant enzyme activities, increase the protein expression of adiponectin receptor 2 and PPAR-alpha, and recover renal function. Conclusion. These results permit us to confirm that gamma Oz is able to modulate PPAR-alpha expression, inflammation, and oxidative stress pathways improving obesity-induced renal disease.